PREPARASI DAN KARAKTERISASI ASPAL POLIMER DARI LIMBAH STYROFOAM DAN KARET BAN MENGGUNAKAN INISIATOR DIKUMIL PEROKSIDA DAN KOMPATIBILIZER DIVENIL BENZENA - Ahmad Hafizullah Ritonga (PROSIDING SEMINAR KIMIA, 2017)
This study aims to prepare and characterize polymer asphalt by utilizing styrofoam waste and tire rubber as an additive to improve the quality of asphalt by using dicumyl peroxide as an initiator and divenil benzene as a compatibilizer between styrofoam and tire rubber. Polymer asphalt is prepared by mixing styrofoam, tire rubber, asphalt, sand aggregate, divenil benzene and dicumyl peroxide, and extruded at 170 °C. The most optimum result was produced on Asphalt-Styrofoam-Rubber Tire (60:35:5) composition, with mechanical strength test of 2.92 MPa, water absorption test of 0.23%. The FTIR spectrum shows a change in the functional group in the hydroxyl group showing the reaction of crosslinking between styrofoam, tire rubber, DVB, with asphalt. Keywords: Styrofoam, Rubber Ban, Asphalt, Divenil Benzene, Dichoxic Peroxide